Improving young indigenous Malaysian children's incidental vocabulary acquisition and oral narrative skills through shared-book reading - Ma'rof, Aini Marina; Redzuan, Ma'rof; Anderson, Richard C.; Ma'rof, Aini Azeqa (Marsland Press, 2012)
This paper is based on a quasi-experimental study which investigated the impact of Shared-book Reading (SBR) on the development of vocabulary and oral narrative skills of young Indigenous Malaysian children learning Malay as a second language. Sixty three (63) Orang Asli children from two first-grade classrooms participated in the study. One of the classes was randomly assigned to implement SBR sessions while the other served as wait-listed control. Prior to the intervention, all students were assessed on a grade-appropriate literacy screening test (LINUS I), a Rapid-automatized naming task (RAN), and a Children’s Nonword Repetition Test (CNRep). After a five-week intervention, all students were assessed on vocabulary and storytelling. Results showed that experiences of SBR accelerated Orang Asli children’s oral Malay language production and increased their level of word-meaning knowledge. Specifically, the SBR group performed significantly better than the control group on the word-defining task. They also produced more coherent, higher quality narratives in a wordless picture story-telling task. They told the stories with greater verbal rate which contained significantly greater vocabulary diversity. These results altogether yield significant implications for the literacy instruction practices of Orang Asli children.